Analisis Implementasi Kebijakan Bantuan Biaya Peningkatan Mutu Pendidikan bagi Mahasiswa dari Keluarga Tidak Mampu - Kusumajati Kusumajati; Teguh Kurniawan (Universitas Medan Area, 2019)
The purpose of this study was to find out the implementation of the policy of cost assistance to increase education for students from disadvantaged families in DKI Jakarta. This research uses descriptive qualitative research by examining secondary data. Improving the quality of human resources is of concern to all parties in entering this era of globalization. Support from various parties is needed by the Indonesian people in facing free competition, one of which is assistance in the field of education because education plays a very important role where the higher the education they have, the higher the quality and competitiveness of these human resources. The DKI Jakarta Provincial Government as one of the regional governments has played its role in supporting education equality especially in providing opportunities for citizens to have higher education issuing policies to provide cost assistance to increase education for students from poor families in 2016 as stipulated in the Regulation of Governor of DKI Jakarta Province Number 133 of 2016 During these 3 years, from 2016-2018, the implementation of the policy of providing cost assistance to increase education faced several obstacles, among others in data collection and distribution of aid.